Status Gizi Bayi 4 – 6 Bulan Yang Mendapatkan Asi Eksklusif Dan Asi Non Eksklusif Di Puskesmas Kolongan Kecamatan Kalawat Kabupaten Minahasa Utara - Rudolf B. Purba; Fred A Rumagit; Rugayu Tahir (Jurnal GIZIDO, 2018)
Exclusive breastfeeding is a baby receiving only direct breastfeeding from biological mother, breast milk or dairy milk until the baby is 6 months old. Non-exclusive breastfeeding is not only breastfed babies but also get other foods other than breastmilk like formula milk. North Sulawesi Province exclusive ASI coverage in 2014 amounted to 38.5% decreased 2015 only 26.3%. The purpose of this research was to know the nutritional status of 4 - 6 months old baby who got exclusive breastfeeding and non exclusive breast milk. The type of research used is descriptive research. The study was conducted for 1 week from 30 May to 6 June 2017 at the Kolongan Community Health Center, Kalawat District, North Minahasa Regency The sample of the study was 4 - 6 months old baby with total sample of 53 babies. Research respondents were infant mothers. The sampling method uses accidental sampling. Data obtained through interviews and direct measurement of nutritional status (BB / U) using baby scales (baby scale). The result of the research is the number of baby samples 4 - 6 months as many as 53 babies. Exclusive breastfeeding of 16 infants. non exclusive breastfeeding of 37 babies, divided into infant formula, breast milk and formula mixture 17 infants. Nutritional status of infants 4 - 6 months total of 53 babies, malnutrition less 4 babies (7.5%), good nutrition 32 babies (60,5%), and 17 more infants (32%).